A carnavalização em Henrique IV: representações da cultura cômica popular através da linguagem - Guerra, Karl George da Silva (2017)
This Master Degree‘s research aims to carry out a semiotic exercise about the comic popular culture of the Middle Ages and the Renaissance applied to the Shakespearean historical drama Henry IV, part I and II. To build the theoretical basis that will support the analyses we used the contributions of Yuri Lotman and Irene Machado concerning the aspects related to the Semiotics of Culture and modellization. For the presentation and discussion about the concepts of popular culture, we used the contributions of the historicist and theorist Peter Burke as well as Mikhail Bakhtin‘s ideas about the theme; and the concepts of ?Party? and ?Symposium? quoted by Sousa. The studies of carnavalization, grotesque realism and the comic also postulated by the Russian theorist Mikhail Bakhtin supported the analysis of the corpora concerning the linguistics phenomena such as oaths, desecrations, praises, rudenesses, carnival dethronements and grotesque aspects of the language that will be discussed along the text to testify our hypothesis that the language of the public square and the grotesque images dialogue in a good way with the historical drama Henry IV. In short, focused on the carnavalization which process, this work analyzed how the language was modelled in the Henry IV, aiming to resignify the comic popular culture that permeates the dramatic construction of this historical drama.